2011
DOI: 10.4061/2011/307875
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effects of Hydrogen in Animal Models of Parkinson's Disease

Abstract: Since the first description of Parkinson's disease (PD) nearly two centuries ago, a number of studies have revealed the clinical symptoms, pathology, and therapeutic approaches to overcome this intractable neurodegenerative disease. 1-methy-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) and 6-hydroxydopamine (6-OHDA) are neurotoxins which produce Parkinsonian pathology. From the animal studies using these neurotoxins, it has become well established that oxidative stress is a primary cause of, and essential for, ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 89 publications
1
13
0
Order By: Relevance
“…Thus, we assessed the effects of ginsenoside Re on 6-OHDA-triggered cellular damage by determining the level of lactate dehydrogenase (LDH) released into the medium and 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT)-based cell viability in SH-SY5Y cells. 6-OHDA significantly increased LDH release into the medium as reported previously [3]. However, this effect was attenuated in the presence of ginsenoside Re ( Figure 3A).…”
Section: Ginsenoside Re Attenuates 6-ohda-triggered Cellular Damagesupporting
confidence: 89%
See 2 more Smart Citations
“…Thus, we assessed the effects of ginsenoside Re on 6-OHDA-triggered cellular damage by determining the level of lactate dehydrogenase (LDH) released into the medium and 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT)-based cell viability in SH-SY5Y cells. 6-OHDA significantly increased LDH release into the medium as reported previously [3]. However, this effect was attenuated in the presence of ginsenoside Re ( Figure 3A).…”
Section: Ginsenoside Re Attenuates 6-ohda-triggered Cellular Damagesupporting
confidence: 89%
“…Oxidative stress is implicated in 6-OHDA-triggered cell damage [3]; thus, we examined the effects of ginsenoside Re on the expression of the antioxidant proteins SOD1, GR, CAT, GPX1, and GPX4 in SH-SY5Y cells. Treatment applied induced only changes at the mRNA level of GPX4 ( Figure 4).…”
Section: Ginsenoside Re Upregulates the Expression Of Gpx4mentioning
confidence: 99%
See 1 more Smart Citation
“…ROS-mediated DA oxidation is also involved in microglial activation and dopaminergic cell death in the substantia nigra [ 51 ]. Besides, oxidative stress-mediated dopaminergic cell death is a major characteristic in toxin-induced PD models [ 52 , 53 ]. In this study, JSE, the water-soluble extract of JS, showed the excellent antioxidant activity of ROS/NO generation and MAO-B inhibitory activity in vitro compared to ginkgo leaf extract that is a known natural MAO-B inhibitor [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we may expect that restoration of dopamine (DA) synthesis and secretion levels may help to ameliorate the PD patients’ symptoms. Furthermore, it is suggested that mitochondrial dysfunction and the associated oxidative stress is the main mechanism responsible for neurodegeneration in PD [77]. DAergic neurons are particularly prone to oxidative damage due to high levels of inherent reactive oxygen species that are produced during DA synthesis or its breakdown by monoamine oxidases [7879].…”
Section: Hif-1 and Parkinson’s Disease (Pd)mentioning
confidence: 99%